Root cutting on growth and yield of oil palm (Elaeis guenesis Jacq.) - Wahyudin, Cecep; Hariyadi; Sudrajat; Yahya, Sudirman; Anwar, Syaiful (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2024)
Root cutting is speculated able to increase nutrient uptake by oil palm. The objective of this study was to investigate the effect of root trimming on the growth, flowering, and yield of oil palm. The research focused on oil palm plants aged five years old in the field. The experiment used a nested design with two key factors: root-cutting depth as the main plot and root-pruning intensity as the subplot. Results showed that root cutting at a depth of 0 to 20 cm from the soil surface followed by cutting intensities of 50% and 75% enhanced plant height at 0, 3, and 9 months after treatment. The treatments did not affect other variables including flowering and yield of oil palm trees. Keywords: bunch weight; cutting intensity; root trimming; sex ratio